Effect of Infographics and E-Book Instructional Packages on Junior Secondary School Students’ Learning Outcomes in Business Studies in Ibadan, Nigeria - Olalude, Olayemi Olusegun; Aremu, Ayotola; Olasunkanmi, Israel Abayomi (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2024)
This research developed instructional packages in the form of infographics and e-books and evaluated their effectiveness on junior secondary school students' learning outcomes (achievement, attitude, and entrepreneurial intention) in Business Studies in Ibadan, Nigeria. Three hypotheses were formulated and tested. A quasi-experimental pretest-posttest control group design was used for the study. Three public junior secondary schools with operational computer labs and backup generators were purposefully selected in Ibadan. Three intact Junior School II classes were randomly assigned to the infographic (n=50), e-book (n=42), and control (n=90) groups. The tools utilised included the Students' Achievement Test (r=0.80), Attitude to Business Studies (r=0.75), and Entrepreneurial Intention (r=0.70) scales. Data were analysed using Analysis of Covariance (ANCOVA) and Bonferroni posthoc tests at a 0.05 significance level.. Results from the analysis revealed that there were significant main effects of infographics and e-book instructional packages on students’ achievement (F(2, 181) = 358.68;p<0.05, partial η2 = 0.64); Students' attitude towards business studies (F(2, 181) = 104.19;p<0.05, partial η2 = 0.54) and entrepreneurial intenti0n (F(2, 181) = 66.93;p<0.05, partial η2 = 0.43). Students in the E-book had the highest adjusted p0st-achievement mean score (38.88) followed by the Infographics group (38.73) and the C0ntr0l group (25.10). Students in the Infographics group had the highest adjusted p0st-attitude mean score (70.14) followed by the e-book group (69.90) and C0ntr0l group (60.64). While students in E-book had the highest adjusted p0st-entrepreneurial intenti0n mean score (68.44) f0ll0wed by the Infographics group (66.63) and C0ntr0l group (61.60) respectively. This study recommends the adoption of infographics and e-book instructional packages in teaching Business Studies to enhance learning outcomes.